Optimasi Kualitas Air Sumur Gali melalui Pemanfaatan Senyawa Bioaktif dari Daun Ageratum conyzoides - riang adeko; Andriana Marwanto; Aplina Kartika Sari; Habibi Hidayat; Ullya Rahmawati (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
The increasing demand for clean water in coastal and rural areas requires affordable and environmentally friendly purification methods. This study investigates the utilization of bioactive compounds from Ageratum conyzoides leaves to enhance the quality of dug well water. Phytochemical screening revealed that the leaves contain tannins, flavonoids, saponins, polyphenols, essential oils, and various secondary metabolites with potential coagulating and antimicrobial properties. Fourier Transform Infrared (FTIR) spectroscopy identified functional groups associated with phenolic, flavonoid, alkaloid, and terpenoid compounds, suggesting their role in natural coagulation processes. Coagulation tests using different dosages (15, 25, and 35 mg) demonstrated a significant reduction in turbidity, with the highest efficiency (68%) achieved at 15 mg dosage. These findings indicate that A. conyzoides leaf extract can serve as a sustainable bio-coagulant for improving dug well water quality. Further studies employing GC-MS and LC-MS are required to optimize compound characterization and strengthen its application in community-scale water treatment.